Caracterização da formação pimenteiras (Devoniano) como unidade potencial para gás folhelho (Shale gas) no sudeste do Piauí - Lima, Nathalia Olimpio de (2016)
This research approaches the description of the Pimenteiras Formation with the purpose of studying the potential of shale gas resources in the Parnaíba Basin. This gas has been insufficiently researched in Brazil, but widespreadly studied throughout the world with the aim to become a new and promising alternative source of unconventional hydrocarbon. The execution of this project counted with a field camp stage, which was responsible for the facies analysis and measurement of gas chromatography in situ. In addition, 7 samples of shale rock were collected along the way and analyzed later on by different laboratory techniques, such as Gamma ray spectrometry, X ray diffraction (XRD), X ray fluorescence (XRF), Scanning electron microscope (SEM) and Total organic carbon (TOC) analysis. In short, the results indicate deposition in a continental shelf environment subjected to storms, with decantation of ductile smectites clay minerals, primary porosity with favourable dimension but unfavourable geometry, low content of organic matter, intermediate conditions of organic matter oxidation, low production of methane, and highlighting the biogenic origin of the organic matter. In addition, for the studied location, the potential of the unconventional gas production is not favourable to the current market conditions.